A Simulation Scheme for Unordered Power Charging Of Electric Vehicles On Distribution Power Network. Issue 5 (March 2019) - Zheng, Zhengxian; Jiang, Yanping; Xu, Yu; Zhang, Pengfei; Shan, Leijin; Chen, Shuqi
Abstract: With the lack of support for new energy electric vehicles (EV) and the continuous introduction of new policies, EV are entering a period of rapid development. However, the large number of unordered access distribution network of EV users in the period will have a great impact on the power distribution network. EV will further aggravate the load peak valley of the grid during peak periods. It may lead to a series of problems such as overload of distribution network line, voltage drop, increase of distribution network loss and overload of distribution transformer. This paper makes an in-depth analysis of the influence of unordered access charging on power distribution network from theoretical and practical perspectives. For example, Network load, voltage, line loss, etc. Based on the analysis results, a smart charging station based on variable distribution is proposed. It is the best solution to solve the current problem by intelligent orderly control method.